Bonn Cathedral - Howe, J. (engraver):::Creator::::::::::::; Tombleson, William, b. ca. 1795 (artist):::Contributor:::::::::::: (London; G. Virtue, 2020)
Steel engraving of the exterior of the Munster in Bonn